2016
DOI: 10.1364/ol.41.005198
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of soliton cascades in fiber amplifiers

Abstract: We study numerically the formation of cascading solitons when femtosecond optical pulses are launched into a fiber amplifier with less energy than required to form a soliton of equal duration. As the pulse is amplified, cascaded fundamental solitons are created at different distances, without soliton fission, as each fundamental soliton moves outside the gain bandwidth through the Raman-induced spectral shifts. As a result, each input pulse creates multiple, temporally separated, ultrashort pulses of different… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Thus, once the effective soliton number has become less than unity, the soliton fission process is eventually terminated [1]. In contrast, when the optical gain is turned on, the dynamics associated with soliton fission becomes substantially different from that of the passive case: The 'pulse remnant' [18], which is the part of the input pulse remaining after the soliton fission or breakup at z = 0.07 m, continues to emit fundamental solitons as shown in Fig. 2(d).…”
Section: A Gain Effects On Scg In the Ad Regimementioning
confidence: 99%
See 2 more Smart Citations
“…Thus, once the effective soliton number has become less than unity, the soliton fission process is eventually terminated [1]. In contrast, when the optical gain is turned on, the dynamics associated with soliton fission becomes substantially different from that of the passive case: The 'pulse remnant' [18], which is the part of the input pulse remaining after the soliton fission or breakup at z = 0.07 m, continues to emit fundamental solitons as shown in Fig. 2(d).…”
Section: A Gain Effects On Scg In the Ad Regimementioning
confidence: 99%
“…That is, the rate-equationbased approach utilized in [9] might be no longer appropriate enough for such extremely fast nonlinear interactions in the AD regime. We note that to date only a handful of numerical or theoretical studies have been carried out on analyzing novel characteristic aspects of SCG in active fibers in the AD regime [12], [18]- [20]. In particular, Lei et al reported that SCG in a Yb-doped fiber (YDF) with AD can be modeled by combining the well-known rate equation and the nonlinear Schrödinger equation (NLSE) when excited by ps pulses [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, fundamental solitons themselves are resistant to fission or any kind of splitting [1,5]. Generally, splitting of a fundamental soliton is only possible if the fiber is tapered [6][7][8] or is doped and pumped to provide amplification [9][10][11][12]. Both of these methods rely on increasing the soliton order to beyond N = 1.5 so that a second-order soliton is formed that splits into two fundamental solitons.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results presented below are accompanied by numerical results obtained from our simulation code. Pulse propagation in the fibers is modeled through the scalar generalized nonlinear Schrödinger equation [21] taking into account dispersion up to third order (TOD), the instantaneous Kerr response, the complete delayed Raman response of silica fibers [22], and the spectral gain calculated from the erbium cross sections and the rate equations solved in the steady state [23]. The model does not include ASE.…”
mentioning
confidence: 99%